Disharmony in Supervision of OJK–DSN-MUI in Implementation of the Murabahah Fatwa - Anisa Prabowo; Fiana Suryaningtyas Wibowo; Nadia Rizqa Setyaningrum; Baidhowi (Takaza Innovatix Labs Ltd., 2025)
The murabahah fatwa is the primary guideline for ensuring compliance of Islamic financial institutions' practices with sharia principles. However, its implementation in Indonesia still faces challenges in the form of disharmonious supervision between the Financial Services Authority (OJK) and the National Sharia Council–Indonesian Ulema Council (DSN-MUI). This difference in authority and oversight mechanisms has the potential to lead to inconsistent fatwa implementation in practice. This study aims to analyze this disharmony and its implications for sharia compliance. The method used is normative juridical with a statutory and conceptual approach. The results indicate that weak coordination and lack of integrated supervision have resulted in suboptimal implementation of the murabahah fatwa, potentially leading to deviations from sharia principles. Therefore, strengthening synchronized supervision is necessary to ensure more effective sharia compliance.